Multimotors Coordination Control Method for Consistent Total Traction Torque of Electric Locomotives - Jianhua Liu; Rui Nie; Zheshu Li (Journal of Advanced Transportation)
Multimotors traction is a common driving mode for electric locomotives. The complexity and variability of the operating environment often cause difficulties for one or some traction motors to output the distributed traction torque, which requires the redistribution of the torque output of multimotors to maintain the total traction torque of all motors at a given constant. To this end, a multimotors coordination control method was proposed for consistent total traction torque of electric locomotives. Through this approach, a traction torque-coordinated control structure was constructed on the basis of energy minimisation with an optimal dynamic adjustment mode. The sliding mode tracking control was developed for each independent motor to improve its dynamic response performance. A simulation verification of motors fault types in two different cases was conducted. The results showed that the proposed method could track the total traction torque in a short time, and the system fluctuations in independent motor coordination process were very small.